2012
DOI: 10.1055/s-0031-1291163
|View full text |Cite
|
Sign up to set email alerts
|

Direct C-H Arylation of Quinones with Anilines

Abstract: We discovered that anilines were suitable for the direct C-H arylation of benzoquinone in the presence of tert-butyl nitrite. This new reaction proceeds through the in situ formation of a diazonium hydroxide species. The coupling can be carried out at room temperature under neutral, additive-free, metal-free, and aqueous conditions, allowing an environmentally friendly procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…ArQs are usually prepared by the addition reaction of the diazonium salts of Ar with quinones, which is known as the Meerwein arylation, a classic method, and the aryl‐coupling reaction of halogenated quinones with the boronic acid ester of Ar in the presence of a transition metal catalyst, which is known as the Suzuki‐Miyaura coupling, a contemporary method . However, considering the instability of the unsubstituted biphenoquinone and the low solubilities of the corresponding halogenated biphenoquinones, the application of the Meerwein arylation and the Suzuki‐Miyaura coupling seemed to be difficult.…”
Section: Resultsmentioning
confidence: 99%
“…ArQs are usually prepared by the addition reaction of the diazonium salts of Ar with quinones, which is known as the Meerwein arylation, a classic method, and the aryl‐coupling reaction of halogenated quinones with the boronic acid ester of Ar in the presence of a transition metal catalyst, which is known as the Suzuki‐Miyaura coupling, a contemporary method . However, considering the instability of the unsubstituted biphenoquinone and the low solubilities of the corresponding halogenated biphenoquinones, the application of the Meerwein arylation and the Suzuki‐Miyaura coupling seemed to be difficult.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Lamblin and Felpin found that a mixture of anilines and t BuONO in aqueous DMSO led to the formation of corresponding diazonium hydroxides. With this observation, the arylation reactions of benzoquinone with in situ generated diazonium hydroxides from anilines and t BuONO were carried out (Scheme ) . This approach avoided the preparation and handling of explosive diazonium salt, and no corrosive HCl was needed.…”
Section: Arylation Of Quinonesmentioning
confidence: 99%
“…101,259-267 Lamblin et al 268 developed a facile route for 2-aryl-1,4benzoquinones (142) via direct C-H arylation of p-quinone (11) with anilines (24) in the presence of tert-butyl nitrite in aqueous DMSO at room temperature under neutral, additive-free and metal-free conditions (Scheme 50). 101,259-267 Lamblin et al 268 developed a facile route for 2-aryl-1,4benzoquinones (142) via direct C-H arylation of p-quinone (11) with anilines (24) in the presence of tert-butyl nitrite in aqueous DMSO at room temperature under neutral, additive-free and metal-free conditions (Scheme 50).…”
Section: Scheme 49 Cobalt Acetylacetonate-catalyzed Synthesis Of Submentioning
confidence: 99%